4n2-12n-1=0

Simple and best practice solution for 4n2-12n-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n2-12n-1=0 equation:



4n^2-12n-1=0
a = 4; b = -12; c = -1;
Δ = b2-4ac
Δ = -122-4·4·(-1)
Δ = 160
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{160}=\sqrt{16*10}=\sqrt{16}*\sqrt{10}=4\sqrt{10}$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-4\sqrt{10}}{2*4}=\frac{12-4\sqrt{10}}{8} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+4\sqrt{10}}{2*4}=\frac{12+4\sqrt{10}}{8} $

See similar equations:

| (12x-3)=(5x+12)=(3x+13) | | 3(t=4)=25.5 | | (12x-3)=(5x+12)=(3x+130 | | 6x-3÷5=10 | | -8-k=8(7k-1) | | 3=r+1/2 | | 5•x+3•x+2=18 | | -1(5x-2)=27 | | 32=4(a-1) | | 6-0.26f=f-3 | | -4(2p-6)=2(1-5p)+6 | | −6x=5x+22 | | 3x+10=(1-7x) | | 7(2n-2)=-(3-3n) | | 52=8b+5b | | 5(4w)=90 | | x+11/3=-5 | | -37-4x=3(1-3x) | | –3(p+8)=–6 | | -(2-8k)=5k+19 | | -2.8x-2.1=−7.14 | | -8-x/6=12 | | 8x+38=x+97 | | 2m(m-5)=m-3 | | 3(-4k-6)+3(2+6k)=-54 | | -3p-7p=5p | | 2(6x+5)=12x–3 | | -5a+7=-35 | | Z=x-140/50 | | 18=-7(7m-7)-3(-5m-1) | | -y+198=286 | | 3(1k-9)=3k+6 |

Equations solver categories